Pengaruh level suplementasi pakan konsentrat terhadap status fisiologis ternak kambing lokal betina yang mengkonsumsi jerami jagung - Kamaria Judan; Yohanis Umbu Laiya Sobang; Ahmad Saleh (Jurnal Peternakan Lahan Kering, 2019)
The purpose of this study is to evaluate the effect of supplementation level of concentrate feed on physiological status of local female goat livestock consuming corn straw. The livestock used in this research is the local female goat livestock sebayak 9 tail with the age range of 4-6 months the average weight of the early livestock 12-15 kg. This study used Completel Randomized Design (CRD) with 3 treatments and 3 replications. The treatment is R0 = corn straw adlibitum: concentrate 200 gram; R1 = corn straw adlibitum: concentrate 400 gram; R2 = corn straw adlibitim: 600 gram concentrate. The results of the analysis of variance (ANOVA) showed that the effect of treatment was not significant (P> 0.05) to the consumption and digestibility of dry matter, organic matter. The from results obtained it can be concluded that the influence of supplementation level of concentrate feed on physiological status of local female goat livestock consuming corn straw showed almost the same effect on rectal temperature temperature, heart rate and respiratory rate.